2017
DOI: 10.1016/j.neulet.2017.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Posture and gaze tracking of a vertically moving target reveals age-related constraints in visuo-motor coupling

Abstract: Previously we have demonstrated that the effect of aging on posture and gaze active tracking of a visual target moving in the horizontal direction is dependent on target’s complexity. In this study, we asked whether a similar phenomenon is present when tracking a visual target moving with varying complexity in the vertical direction. Ten young (22.98 ± 2.9 years) and 10 older adults (72.45 ± 4.72 years) tracked for 120 s, a visual target moving vertically by shifting their bodyweight in the anterior-posterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
4
7
0
Order By: Relevance
“…Tracking of the chaotic target resulted in lower coherence, greater target overshooting, and a longer phase lag between the target and the CoP motion when compared to periodic target tracking. These results confirm previous findings from our laboratory showing that voluntary, sagittal plane sway synchronizes better with predictable (i.e., periodic) target motion than less predictable (i.e., chaotic) target motion when actively tracking a vertically moving target [12,16]. It could be suggested that postural tracking of the chaotic target imposed more extensive visuo-motor processing due to the less predictable nature of the target's motion, which may have kept participants more actively engaged in the tracking task due to the continuous need to attend to the target motion.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Tracking of the chaotic target resulted in lower coherence, greater target overshooting, and a longer phase lag between the target and the CoP motion when compared to periodic target tracking. These results confirm previous findings from our laboratory showing that voluntary, sagittal plane sway synchronizes better with predictable (i.e., periodic) target motion than less predictable (i.e., chaotic) target motion when actively tracking a vertically moving target [12,16]. It could be suggested that postural tracking of the chaotic target imposed more extensive visuo-motor processing due to the less predictable nature of the target's motion, which may have kept participants more actively engaged in the tracking task due to the continuous need to attend to the target motion.…”
supporting
confidence: 91%
“…The predictable signal was a sinewave with a single frequency (f) set at 0.25 Hz that was generated using the sin function [sine = sin(2pi × f × t)]. This particular frequency was selected because it was the dominant frequency of intuitive, self-paced voluntary sway based on prior studies [12,16] and pilot testing. The less predictable signal was derived from a Lorenz attractor according to the parameters: σ = 10, β = 8/3, and r = 28 and the initial conditions: x0 = 0.1, y0 = 0.1, and z0 = 0.1.…”
Section: Apparatus Stimuli and Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter deficits can be targeted by multisensory processing strategies that can facilitate performance since they require the additional recruitment of parietal and prefrontal areas, which compensates for the sensory impairments in bottom‐up processing during executive control (i.e., Hemispheric Asymmetry Reduction in OLDer adults—HAROLD model) . Multisensory stimulation could, therefore, enhance cognitive processing, assist the elderly to rely on more than one modality during gait and postural control, and possibly yield transfer effects in critical everyday tasks, including visuomotor coordination, balance maintenance and gait control, estimation of body motion in space, detection of changes in head acceleration, perception of peripersonal space, and reduction of cognitive‐motor interference in dual tasking when the secondary task includes a visualization component …”
Section: Interactions Between Gait Cognition and Perception In Agingmentioning
confidence: 99%
“…The periodic signal was a sinewave with a single frequency (f) set at 0.25 Hz that was generated using the sin function . The particular frequency was selected because this is the dominant frequency of natural, self-paced voluntary sway 30 , 31 . The chaotic signal was derived from a Lorenz attractor, according to the parameters: σ = 10, β = 8/3 and r = 28 and the initial conditions: x 0 = 0.1, y 0 = 0.1 and z 0 = 0.1.…”
Section: Methodsmentioning
confidence: 99%